2019
DOI: 10.1186/s43046-019-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient lymph node assessment in gastric adenocarcinoma

Abstract: Background: This study aimed to investigate the sufficient (≥ 16) lymph node assessment in 449 patients with gastric adenocarcinoma and literature review. Methods: Four hundred and forty-nine patients with pathologically confirmed locoregional invasive gastric adenocarcinoma from 2004 to 2013 were included. A standard surgical resection was performed for all the patients with (n = 16) or without (n = 433) neoadjuvant treatment. Results: In this study, 301 men and 148 women with a median age of 58 (range 21-88)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Some study has noticed a stage-specific lymph node retrieving may present diverse survival benefits in gastric cancer [ 18 ]. A study of 449 gastric cancer patients from Iran reported that the median total number of examined lymph nodes were 9 (ranging 0–55), with only 21.2% patients has adequate lymph nodes yielding ( n ≥ 16) [ 27 ]. The National Comprehensive Cancer Network (NCCN) guideline suggests that a minimum 15 resecting lymph nodes is required, based on the evidence that 15 lymph nodes is the threshold number with a survival benefit [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some study has noticed a stage-specific lymph node retrieving may present diverse survival benefits in gastric cancer [ 18 ]. A study of 449 gastric cancer patients from Iran reported that the median total number of examined lymph nodes were 9 (ranging 0–55), with only 21.2% patients has adequate lymph nodes yielding ( n ≥ 16) [ 27 ]. The National Comprehensive Cancer Network (NCCN) guideline suggests that a minimum 15 resecting lymph nodes is required, based on the evidence that 15 lymph nodes is the threshold number with a survival benefit [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, insufficient LN assessment is often apparent in the current literature[ 20 ]. For example, in his review of 15 studies, which included 27,942 patients, Khanjani et al [ 5 ] showed that only 52.2% of the patients received an adequate nodal evaluation, given the AJCC’s current recommendation to assess at least 16 LNs[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the national guidelines, many studies particularly those from Western countries continue to show high rates of inadequate nodal assessment[ 5 - 7 ]. To mitigate the effects of stage migration and survival inaccuracies in patients with locally advanced gastric cancer, use of the ratio of positive to total LN has been proposed[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many conditions can lead to inadequate LN harvest. It is estimated that only one-fifth of the patients with GC have an adequate number of LN examined in Iran, 26 while more than 15 LNs are examined in 64% of the patients in the USA. 25 The LNR and LODDS staging methods do not require an adequate number of LNs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%